Pengembangan Kompetensi Sumberdaya Manusia Melalui Pelatihan Digital Marketing Di Desa Sumber Rejo Kabupaten Batubara - Purba, Melfrianti Romauli; Sihombing, Yeni Rafita; Nainggolan, Tuty; Permana, Jaka; Purba, Lenta Friska (Abdimas Mandalika, 2025)
Abstract:  The current era of digitalization presents significant opportunities for MSMEs (Micro, Small, and Medium Enterprises) to expand their market reach through digital platforms. Digital marketing has become one of the strategic solutions to enhance the competitiveness of local products, introduce them to broader markets, and increase community income. The objective of this community service program is to provide an understanding of the basic concepts of digital marketing, including digital marketing strategies, benefits, and their application across various types of businesses. The implementation methods for this activity include lectures, question-and-answer sessions, practical exercises, and discussions. The expected outcome of this program is that the training will have a tangible impact on improving the competencies of human resources in Sumber Rejo Village, particularly in utilizing digital marketing to support local business development and foster the community's economic growth.Abstrak: Era digitalisasi saat ini membuka peluang besar bagi pelaku UMKM untuk memperluas jangkauan pasar mereka melalui platform digital. Digital marketing menjadi salah satu solusi strategis untuk meningkatkan daya saing produk lokal, memperkenalkan produk ke pasar yang lebih luas, dan meningkatkan pendapatan masyarakat. Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah untuk memberikan pemahaman mengenai konsep dasar digital marketing, termasuk strategi pemasaran digital, manfaat, dan penerapannya dalam berbagai jenis usaha. Metode pelaksanaan dalam kegiatan ini adalah ceramah, tanya jawab, praktik dan diskusi. Hasil dari kegiatan pelatihan meningkatnya kompetensi sumber daya manusia di Desa Sumber Rejo, khususnya dalam memanfaatkan digital marketing untuk mendukung pengembangan usaha lokal dan pertumbuhan ekonomi masyarakat.